How Parental Predictors Jointly Affect the Risk of Offspring Congenital Heart Disease: A Nationwide Multicenter Study Based on the China Birth Cohort - Zhang, Man; Sun, Yongqing; Zhao, Xiaoting; Liu, Ruixia; Yang, Bo-Yi; Chen, Gongbo; Zhang, Wangjian; Dong, Guang-Hui; Yin, Chenghong; Yue, Wentao (Frontiers in Cardiovascular Medicine, 2022)
Objective: Congenital heart disease (CHD) is complex in its aetiology, the genetic causes have been investigated, whereas the non-genetic factors related studies are still limited. We aimed to identify dominant parental predictors and develop a predictive model as well as nomogram for the risk of offspring CHD. Methods: This was a retrospective cohort study from November 2017 to December 2021 covering 44578 participants, of which those from 4 hospitals in eastern China were assigned into the development cohort and those from 5 hospitals in central and western China were used as the external validation cohort. Univariable and multivariable analyses were used to select the dominant predictors of CHD among demographic characteristics, lifestyle behaviors, environmental pollution, maternal diseases history, and the current pregnancy information. Multivariable logistic regression analysis was used to construct model and nomogram using the selected predictors. The predictive model as well as the nomogram were both validated internally and externally. A web-based nomogram was developed to predict patient-specific probability for CHD. Results: Dominant risk factors for offspring CHD included increased maternal age [odds ratio (OR): 1.14, 95% CI: 1.10-1.19], increased paternal age (1.05, 95% CI: 1.02-1.09), maternal secondhand smoke exposure (2.89, 95% CI: 2.22-3.76), paternal drinking (1.41, 95% CI: 1.08-1.84), maternal pre-pregnancy diabetes (3.39, 95% CI: 1.95-5.87), maternal fever (3.35, 95% CI: 2.49-4.50), assisted reproductive technology (2.89, 95% CI: 2.13-3.94), and environmental pollution (1.61, 95% CI: 1.18-2.20). And higher household annual income (100,000-400,000 CNY: 0.47, 95% CI: 0.34-0.63; >400,000 CNY: 0.23, 95% CI: 0.15-0.36), higher maternal education level (13-16 years: 0.68, 95% CI: 0.50-0.93; ≥17 years: 0.87, 95% CI: 0.55-1.37), maternal folic acid (0.21, 95% CI: 0.16-0.27) and multivitamin supplementation (0.33, 95% CI: 0.26-0.42) were protective factors. The nomogram showed good discrimination in both internal (AUC: 0.843) and external validations (development cohort: 0.849, external validation cohort: 0.837). The calibration curves demonstrated good agreement between nomogram-predicted probability and actual presence of CHD. Conclusions: We revealed dominant parental predictors and presented a web-based nomogram for the risk of offspring CHD, which could be utilized as an effective tool for quantifying individual risk of CHD and promptly identifying high-risk population.